Perceived Job Performance and Constraints Hindering Performance of Krishi Vigyan Kendras in Mizoram - P. Lalhmachhuana and Loukham Devarani (Indian Journal of Extension Education, 2017)
The effectiveness of any organisation depends on the performance of the manpower engaged. This study was conducted inthree KVKs of Mizoram viz., Kolasib, Lunglei and Aizwal with the objective to assess the perceived job performance ofthe scientific and technical staff of the KVKs and constraints faced by the staff which hinder their performance. Majority(66.67%) of staff were found to be in medium job performance category. Performance was found to be most effective inpresenting and discussing field problems to farmers, conducting need based training programmes, attending officialmeetings regularly and communicating solutions to farmers on field problems but found to be low in getting samplestested (fertilizers /plant protection chemical /seed / soil & water), providing advisory through ICT and ensuring that ruralyouths member within the KVK got a stable and reliable job. No special budgetary provision for conduct of demonstrationunits, delay in releasing salary and lack of man power were the major constraints reported.